(untitled) (Gestão & Regionalidade, 2025)
Difficulties in influencing the institutional environment create the opportunity for collective action through associations representing interests. The objective is understanding what influences associates’ satisfaction with interest representation services. The approach is qualitative-quantitative. The primary data in the agricultural inputs distribution sector originate from a perception questionnaire and in-depth interviews. The results indicate that the quality of services influences members’ satisfaction. Members have confidence in representation services and value the association’s reputation, impacting quality and trust. Social and trust relational benefits can strengthen quality and trust relationships with the satisfaction of interest representation services. The research contributes to corporate political activities through private interest representation services in a country where lobbying is not regulated. In practical terms, it helps managers of representative organizations and their associates to determine sectoral collective agendas.